Needs Analysis of Student Worksheets to Develop Collaborative Skills in Learning Science - Nurul Saadah Agustina; Wahyu Sopandi; Atep Sujana (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Learning in schools must develop students collaborative skills, student worksheet as a learning tool is considered capable of encouraging students to develop these skills. The purpose of this study was to describe the needs of student worksheets that develop collaboration skills in learning science in elementary schools. This research was conducted using a qualitative descriptive method involving teachers. Data collection was carried out using instruments in the form of questionnaires and student worksheet assessments from the questionnaire fillers. Research data is processed by determining the percentage value of the results of questionnaires and analysis of student worksheet based on structure, preparation standards, based on certain models and the emergence of collected collaboration skills. The results showed that most of the existing student worksheet did not meet standards, were not based on a particular learning model, and had not trained students' collaboration skills. This research shows the need to develop worksheets that are able to train students' collaboration skills.